The commuting distribution - Jos Van Ommeren (European Regional Science Association (ERSA), 2004)
In this paper we analyse the commuting distribution from a job search perspective. We have examined under which conditions the commuting distribution is unimodal which is one of the stylised facts of commuting. It appears that a necessary condition is that space is two-dimensional. Furthermore, one of the following ingredients is sufficient: on-the-job mobility, spatiality-differentiated search or heterogeneity of jobs. Residential mobility does not appear to explain the shape of commuting density function as we observe it. JEL classification: R20, R64, J64 Keywords: commuting, search, mobility
Keywords: R20; R64; J64; 330; commuting; search; mobility